Management of factor Xa inhibitor–related traumatic non‐intracranial bleeding events with andexanet alfa or four‐factor prothrombin complex concentrate in a US multicenter observational study - Paul P. Dobesh; Craig I. Coleman; Mark Danese; Eva Lesén; Raymond C. Chang; Onivefu Odelade; Gregory J. Fermann (Journal of the American College of Emergency Physicians Open, 2024)
Abstract Objectives This study describes clinical characteristics and management strategies for patients with factor Xa (FXa) inhibitor–related traumatic non‐intracranial bleeds who were treated with andexanet alfa or four‐factor prothrombin complex concentrate (4F‐PCC). Methods An observational cohort study (ClinicalTrials.gov Identifier: NCT05548777) was conducted using electronic health records from 354 US hospitals. Included patients were hospitalized with rivaroxaban‐ or apixaban‐related bleeding, had received andexanet alfa or 4F‐PCC treatment during their hospitalization, and were discharged between May 2018 and September 2022. This analysis was performed in the subgroup of patients with traumatic non‐intracranial critical compartment/non‐compressible bleeds or other traumatic bleeds. Results The study population included 250 patients (andexanet alfa, n = 116; 4F‐PCC, n = 134). Critical compartment bleeds were the most common (86.8%), with retroperitoneal bleeds the most common subtype (30.9%). Most patients were admitted via the emergency department (82.0%). The median time from presentation to reversal/replacement treatment was 2.7 (interquartile range, 1.2, 6.6) h. For patients treated with andexanet alfa, 63.8% were administered the low‐dose regimen. For 4F‐PCC, a median of 2000 total units was administered per patient. Other treatment strategies used included intravenous fluids (26.0%), fresh frozen plasma (16.0%), and packed red blood cells (13.2%). Prior to hospital discharge, oral anticoagulants were restarted in 20.4% of patients. Overall, 25 (10.0%) patients died in hospital. Conclusion This analysis provides insights into the clinical characteristics and management strategies, including time to treatment, for patients treated with andexanet alfa or 4F‐PCC while hospitalized for FXa inhibitor–related traumatic bleeds.